Desain dan Evaluasi Pembelajaran Blended Learning Berbasis WhatsApp Group (WAG) - ansori, miksan (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2016)
Blended learning as one of the 21st century learning always interesting to be discused more deeply. The extend of blended learning scope so the study never dries. Many sides need more critical dan detailed discussion in order to give a stronger perspective, to enrich the science of blended learning and become the reference of education practicioners in practicing it.This article discusses the dedign and evaluation of blended learning using WhatsApp Group (WAG) application in the context of learning in college. Design will contain learning activities and media used. While the evaluation is intended to determine the result of blended learning in achieving learning objectives. Detailed activities to give a detailed perspective of how blended learning is applied.